2019
DOI: 10.1016/j.prdoa.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeting neurons in the gastrointestinal tract to treat Parkinson's disease

Abstract: Background Parkinson's disease (PD) is associated with α-synuclein (αS) aggregation within the enteric nervous system (ENS) and constipation. Squalamine displaces proteins that are electrostatically bound to intracellular membranes and through this mechanism suppresses aggregation of αS monomers into neurotoxic oligomers. Objective We sought to evaluate the safety of ENT-01 oral tablets (a synthetic squalamine salt), its pharmacokinetics, and its effect on bowel functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The results of the first phase 1/2a clinical trial using squalamine as ENT-01 in an open label study involving 50 patients (RASMET, identifier NCT03047629) have been published. 72 ENT-01 restored bowel motility in over 80% of PD patients with severe constipation. This observation indicates that despite bowel dysfunction in some cases for almost 60 years, the functioning of ENS in PD patients can be restored, and is not, as commonly believed, irreversibly damaged.…”
Section: Potential Of Aminosterols As Ad and Pd Drugs And Future Pers...mentioning
confidence: 96%
“…The results of the first phase 1/2a clinical trial using squalamine as ENT-01 in an open label study involving 50 patients (RASMET, identifier NCT03047629) have been published. 72 ENT-01 restored bowel motility in over 80% of PD patients with severe constipation. This observation indicates that despite bowel dysfunction in some cases for almost 60 years, the functioning of ENS in PD patients can be restored, and is not, as commonly believed, irreversibly damaged.…”
Section: Potential Of Aminosterols As Ad and Pd Drugs And Future Pers...mentioning
confidence: 96%
“…In mid-2018 we completed a 50-patient open label Phase 2a clinical study (RASMET) evaluating ENT-01 for the treatment of constipation associated with PD [50]. ENT-01 is an orally administered synthetic salt of squalamine, a cationic aminosterol originally isolated from the liver and gall bladder of the dogfish shark.…”
Section: Targeting ␣S Within the Enteric Nervous System To Treat Parkmentioning
confidence: 99%
“…After taking squalamine in the PD mouse model, the excitability of intrinsic primary afferent neurons of ENS can be rapidly restored (West et al, 2020 ). A double-blind, placebo-controlled study also confirmed that oral tablets of squalamine are safe and significantly improve bowel function in PD-related constipation (Hauser et al, 2019 ). Together, these drugs may provide some promise in clinical trials but need to be evaluated further.…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 84%